2018
DOI: 10.1093/biolre/ioy175
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow-derived cells or C-X-C motif chemokine 12 (CXCL12) treatment improve thin endometrium in a mouse model†

Abstract: Successful implantation and pregnancy is dependent on sufficient endometrial growth during each reproductive cycle. Here we report the therapeutic effect of either bone marrow-derived cells or the stem cell chemo-attractant CXCL12 on endometrial receptivity in a murine ethanol induced thin endometrium model. Endometrial epithelial area was significantly increased in mice treated with BMDCs, CXCL12 or by co-treatment with both compared with PBS treated controls. Ki-67 and CD31 immunoreactivity was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 48 publications
0
36
0
1
Order By: Relevance
“…BMDSC treatment increased endometrial thickness and the number of capillaries and glands, and also modified the expression of various markers of integrin and leukemia inhibitor factor, which are involved in endometrial receptivity. A recent study demonstrated similar findings, in which systemic treatment with BMDCs significantly increased cellular proliferation and vascularization in uterine tissue in mice with induced thinning of the endometrium compared to controls [ 24 ]. In addition, a modest improvement of fertility outcomes was found in mice treated with BMDCs, together with favorable modifications of histological or biochemical markers of uterine receptivity.…”
Section: Role Of Bmdscs In Animal Models Of Endometrial Injurymentioning
confidence: 54%
See 1 more Smart Citation
“…BMDSC treatment increased endometrial thickness and the number of capillaries and glands, and also modified the expression of various markers of integrin and leukemia inhibitor factor, which are involved in endometrial receptivity. A recent study demonstrated similar findings, in which systemic treatment with BMDCs significantly increased cellular proliferation and vascularization in uterine tissue in mice with induced thinning of the endometrium compared to controls [ 24 ]. In addition, a modest improvement of fertility outcomes was found in mice treated with BMDCs, together with favorable modifications of histological or biochemical markers of uterine receptivity.…”
Section: Role Of Bmdscs In Animal Models Of Endometrial Injurymentioning
confidence: 54%
“…The authors concluded that CXCL12 augmentation induced stem cell engraftment into the uterus, reduced fibrosis formation with uterine function enhancement (litter size and decreased time to conceive), and possibly improved pregnancy in AS mice without supplemental BM transplantation. A recent study demonstrated a comparable effect of CXCL12 with BMDCs in mice with thin endometrium, observing significant improvements in the regeneration of endometrial histology, expression of biochemical markers, and fertility outcomes in both treatment groups [ 24 ]. These lines of evidence indicate the potential therapeutic value of CXCL12 in stem cell-related therapy based on its biological action for stem cell mobilization, suggesting that it may serve as an alternative or replacement for stem cell transplantation [ 17 ].…”
Section: Chemoattractantsmentioning
confidence: 99%
“…A pharmacological approach to increase endometrial progenitor populations could be useful in the management of other intractable reproductive disorders. For example, in a murine model of thin endometrium, tissue regeneration and pregnancy rates were increased following treatment with either BMDC or SDF-1 [38]. A recent non-controlled study reported that autologous cell therapy in conjunction with hormonal replacement therapy temporarily improves endometrium thickness, as well as the volume and duration of menses, in patients with refractory Asherman's syndrome or endometrial atrophy [59].…”
Section: Discussionmentioning
confidence: 99%
“…However, bone marrow transplantation studies in humans and mice have provided compelling evidence that endometrial regeneration and homoeostasis also depend, at least partly, on recruitment and engraftment of bone marrow-derived cells (BMDC) and their subsequent differentiation into non-hematopoietic endometrial lineages, including endothelial, stromal and epithelial cells [32À36]. Stromal cell-derived factor-1a (SDF-1), also known as CXCL12, is a potent chemotactic factor that mediates mobilization of BMDC and homing to the endometrium in response to tissue injury and rising oestradiol levels [37,38]. However, SDF-1 is proteolytically inactivated by dipeptidyl-peptidase IV (DPP4), a ubiquitous aminopeptidase expressed both as a cell surface-bound protein and in soluble form [39].…”
Section: Introductionmentioning
confidence: 99%
“…This results in enhancement of cell-cell adhesion between the embryo and endometrium, trophoblast invasion, and endothelial angiogenesis [64,65]. Recently, it has been reported that invasive CXCL12 injection to the uterine muscle layer demonstrated a bene cial effect for endometrial regeneration on the improvement of endometrial receptivity of thin endometrium with the combined treatment with bone marrow-derived mesenchymal stem cells [66]. CXCL12 was suggested as a potent chemoattractant of bone marrow-derived mesenchymal stem cells mediating immunomodulatory actions and promoting angiogenesis [67].…”
Section: Discussionmentioning
confidence: 99%